Assessing the Healthcare and Harm Reduction Needs Among Women and Men Who Smoke Crack Cocaine - Smith, Kathryn (Université d'Ottawa / University of Ottawa, 2011)
This thesis was undertaken to assess the characteristics of individuals who smoke crack cocaine and to examine the health-related risks and healthcare needs of this population. A literature review of 147 published articles was conducted to synthesize evidence regarding behaviours associated with crack use and to assess the risks of disease transmission through crack smoking behaviours. Qualitative interviews were subsequently conducted with thirty Ottawa residents who smoke crack to learn about their experiences with healthcare and harm reduction services. Results identified barriers related to accessing primary healthcare and drug treatment programming among people who smoke crack and gaps within existing harm reduction services. Individuals who smoke crack represent a marginalized population who are often missed through traditional health promotion and harm reduction programming. There is a need for increased coverage of current programming and a reduction of factors which currently hinder the delivery and effectiveness of crack-specific harm reduction programs.
Keywords: Crack cocaine; Health service access; HIV transmission prevention; HCV transmission prevention; Harm reduction